Assessment of biomarkers in pediatric atopic dermatitis by tape strips and skin biopsies - Andersson, Anna Maria; Sølberg, Julie; Koch, Anders; Skov, Lone; Jakasa, Ivone; Kezic, Sanja; Thyssen, Jacob Pontoppidan (Allergy (Copenhagen), 2022)
Background The cytokine profile of atopic dermatitis (AD) depends on age, ethnicity, and disease severity. This study examined biomarkers in children with AD collected by tape strips and skin biopsies, and examined whether the levels differed with filaggrin genotype, disease severity, and food allergy. Methods Twenty‐five children aged 2–14 years with AD were clinically examined. Skin biopsies were collected from lesional skin and tape strips were collected from lesional and non‐lesional skin. We analyzed natural moisturizing factor (NMF) and 17 immune markers represented by mRNA levels in skin biopsies and protein levels in tape strips. Common filaggrin gene mutations were examined in all children. Results The cytokine profile in lesional skin was dominated by a T helper (Th) 2 response in skin biopsies, and by a general increase in innate inflammation markers (interleukin (IL)‐1α, IL‐1β, IL‐8, IL‐18) along with TARC and CTACK in tape strips. The levels of TARC, CTACK, IL‐8, IL‐18 showed significant correlation with AD severity in both lesional and non‐lesional tape stripped skin, while no significant correlations were observed in skin biopsy data. In tape strips from lesional and non‐lesional skin, the levels of NMF and selected cytokines differed significantly between children with and without FLG mutations and food allergy. Conclusion Sampling of the stratum corneum with non‐invasive tape strips can be used to identify biomarkers that are associated with disease severity, food allergy and FLG mutations. Skin biopsies showed robust Th2 signature but was inferior for association analysis regarding severity. Twenty‐five children were examined with skin biopsies from lesional skin and tape strips from lesional and non‐lesional skin. Skin biopsies showed Th2 response and tape strips showed general innate response. Tape strips were superior compared to skin biopsies in detecting biomarker differences related to AD severity, FLG mutations, and food allergy. Abbreviations: AD, atopic dermatitis; CTACK, cutaneous T cell‐attracting chemokine; FLG‐mutation, children with filaggrin gene mutation; LS, lesional skin; NL, non‐lesional skin; TARC, thymus and activation‐regulated chemokine.